Wealth Creation without Pollution (IWA Publishing, 2022)
The development of eco-industrial parks and associated ‘ecological industry’ concepts offer progressive integrated approaches to resolve pollution problems from effluents and wastes of all kinds. Most industry however is now located in business parks and industrial estates, with relatively few industries having direct discharges of process effluents to the water environment. But that does not mean no pollution. Many of these estates are very large, with many companies of all kinds spread over extensive areas. All have surface water drainage and stormwater runoff is often contaminated by many diffuse sources. Wealth Creation without Pollution is the culmination of several years of deliberations by academics and regulators, engaging with industrial and commercial sectors to characterise and quantify environmental problems and identify best practice solutions. Equally important have been efforts to explore sufficiently flexible regulatory regimes that offer effective means to prevent pollution and achieve good working environments in which industry and commerce can flourish. This book explores how modern industries are striving towards more sustainable practices, with case studies of impacts and of greener industry practices, as well as philosophical and policy papers. The role of regulators, planners and government in fostering a greener industrial base is also examined. Wealth Creation without Pollution is a valuable text book for environmental science and engineering students, and a useful resource for industrial architects, developers and practitioners.